Simultaneous Spin‐Crossover Transition and Conductivity Switching in a Dinuclear Iron(II) Coordination Compound Based on 7,7′,8,8′‐Tetracyano‐p‐quinodimethane - Ishikawa, Ryuta; Ueno, Shuya; Nifuku, Shoei; Horii, Yoji; Iguchi, Hiroaki; Miyazaki, Yuji; Nakano, Motohiro; Hayami, Shinya; Kumagai, Shohei; Katoh, Keiichi; Li, Zhao‐Yang; Yamashita, Masahiro; et al. (Chemistry : a European journal, 2020)
The reaction of Fe(OAc)2 and Hbpypz with neutral TCNQ results in the formation of [Fe2(bpypz)2(TCNQ)2](TCNQ)2 (1), in which Hbpypz=3,5‐bis(2‐pyridyl)pyrazole and TCNQ=7,7′,8,8′‐tetracyano‐p‐quinodimethane. Crystal packing of 1 with uncoordinated TCNQ and π–π stacking of bpypz− ligands produces an extended two‐dimensional supramolecular coordination assembly. Temperature dependence of the dc magnetic susceptibility and heat capacity measurements indicate that 1 undergoes an abrupt spin crossover (SCO) with thermal spin transition temperatures of 339 and 337 K for the heating and cooling modes, respectively, resulting in a thermal hysteresis of 2 K. Remarkably, the temperature dependence of dc electrical transport exhibits a transition that coincides with thermal SCO, demonstrating the thermally induced magnetic and electrical bistability of 1, strongly correlating magnetism with electrical conductivity. This outstanding feature leads to thermally induced simultaneous switching of magnetism and electrical conductivity and a magnetoresistance effect. Best combination! A supramolecular coordination assembly composed of FeII ladders and partially charged TCNQ radicals undergoes thermally induced simultaneous switching of magnetism and electrical conduction (SCO=spin crossover, TCNQ=7,7′,8,8′‐tetracyano‐p‐quinodimethane). This material also exhibits a magnetoresistance effect.